High-purity low-fluorine white carbon black and preparation method thereof
Patent Information
- Application Number
- CN202610956536.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-08-18
AI Technical Summary
[0005]本发明的目的是针对现有含氟硅渣资源化工艺能耗高、易产生氟化氢有毒气体、氟杂质脱除不彻底、金属杂质共溶、成品颗粒易团聚、纯度低等缺点,提供一种低能耗、绿色环保、高纯度、低氟、高分散性白炭黑制备方法
1.本发明摒弃传统高温煅烧活化方式,采用常温机械力活化手段处理原料,无氟化氢气体产生,全过程清洁环保、无二次污染;
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of silica preparation technology, and particularly relates to an industrial preparation method for high-purity, low-fluorine silica using fluorinated silicon slag, a byproduct of fluorochemicals, as raw material, through mechanical activation, composite alkali leaching, graded impurity removal, low-temperature crystallization, and surface modification. Background Technology
[0002] Silica, a hydrated amorphous silica, is one of the most widely used inorganic reinforcing and functional fillers in the industrial field. It possesses a large specific surface area, well-developed pore structure, abundant surface hydroxyl groups, excellent chemical stability, outstanding reinforcing performance, resistance to acid and alkali corrosion, and good insulation properties, making it widely used in industries such as rubber, coatings, pharmaceuticals, and fine chemicals. In the wet process of producing hydrogen fluoride and aluminum fluoride in fluorochemicals, a large amount of byproduct silica slag is generated. This solid waste is based on amorphous silica with a dense glassy coating layer on the surface and contains impurities such as soluble fluoride salts, alumina, and iron oxide. The indiscriminate dumping of silica slag not only wastes silicon resources but also causes irreversible environmental pollution such as soil acidification and excessive fluoride levels in groundwater due to the easy migration and diffusion of fluoride ions by rainwater leaching. Some components also slowly decompose in the environment, releasing harmful gases, seriously threatening the safety of surrounding ecosystems and human health. Furthermore, it places enormous environmental disposal pressure and economic costs on enterprises. Therefore, the harmless, high-value resource utilization of fluorinated silica slag is of significant engineering importance.
[0003] There are four main types of processes for preparing silica from silicon slag, but all have significant technical drawbacks: The first type is the high-temperature roasting and impurity removal process, which is energy-intensive, and under high-temperature conditions, bound fluorine easily decomposes to generate corrosive hydrogen fluoride gas, posing a significant environmental risk. The fluorine content of the finished product is generally higher than 100 ppm, which cannot meet the requirements for high-end materials. The second type uses a single strong acid or strong alkali leaching process, which dissolves silicon, iron, and aluminum indiscriminately, resulting in high impurity removal pressure. The specific surface area of the finished product is generally lower than 200 m² / g, and powder agglomeration is severe. The third type is a one-step co-precipitation impurity removal process, which uses a single precipitant to remove fluorine and metal ions simultaneously. This process has poor impurity selectivity, and the fluoride precipitate has weak lattice stability, making it prone to reverse desorption precipitation. The fourth type is a high-temperature acidification crystallization process, with a conventional crystallization temperature of 80~90℃. At high temperatures, silica monomers rapidly and disorderly polymerize, resulting in large particles, uneven pore size, and poor product reinforcing properties. In addition, existing processes generally suffer from industrial drawbacks such as high mother liquor salt content, difficult circulation, and high reagent consumption.
[0004] Therefore, developing green and efficient new resource utilization processes for the harmless treatment, efficient purification and high-value resource utilization of fluorinated silicon slag is crucial, as it offers significant environmental, economic, and engineering application benefits. Summary of the Invention
[0005] The purpose of this invention is to address the shortcomings of existing processes for the resource utilization of fluorinated silicon slag, such as high energy consumption, easy generation of toxic hydrogen fluoride gas, incomplete removal of fluorine impurities, co-dissolution of metal impurities, easy agglomeration of finished product particles, and low purity. This invention provides a method for preparing precipitated silica that is low in energy consumption, environmentally friendly, high in purity, low in fluorine, and highly dispersible.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing high-purity, low-fluorine silica includes the following steps: S1. Raw material pretreatment and activation: Place the silicon slag in a ball mill for ball milling and activation; S2. Selective extraction of silicon components by composite alkali: NaOH and Na2CO3 are prepared into a composite alkali solution. The activated silicon slag is mixed with the composite alkali solution and reacted under closed conditions. The mixture is then filtered under vacuum while hot to separate the filter residue containing iron and aluminum impurities. The sodium silicate filtrate is collected, and the silicon dissolution rate is ≥92%. S3. Filtrate fractionation and impurity removal: This includes two stages of impurity removal: directional fluoride fixation and chelation metal removal, to obtain a purified sodium silicate filtrate containing free F. - It belongs to the category of strong coordinating ions, with a coordinating ability stronger than most conventional metal chelating agents. - Will first with Fe 3+ Al 3+ Once stable fluorine complexes / fluorides are formed (such as Na3AlF6, FeF3); when a chelating agent is subsequently added, on the one hand, the free chelating agent will be absorbed by the residual fluorine. - Competition and combination; on the other hand, the existing metal-fluorine complexes have high bond energies and are difficult to break down by chelating agents, making it impossible to effectively remove metal impurities and significantly reducing the thoroughness of impurity removal; the strategy of this invention is to first remove free F - When all components are solidified into an inert solid phase, coordination competition is eliminated, allowing the chelating agent to act specifically on the target metal ions and achieve targeted impurity removal. S4. Nucleation and Aging: The refined sodium silicate filtrate is diluted and acidified by adding dilute sulfuric acid dropwise at 30-40℃, adjusting the pH to 9.0-9.5. Stirring generates silica crystal nuclei. The nucleation temperature is low, and the reaction is slow, resulting in a large number of fine silica crystal nuclei. Simultaneously, the surface activity of the particles is reduced, preventing them from sticking together (hard agglomeration) from the source, laying the foundation for a high specific surface area. Low-temperature aging also reduces side reactions, resulting in higher product purity. The temperature is then lowered to 20-25℃, and acidification is continued to adjust the pH to 6.5-7.0. Aging yields a silica suspension. Low-temperature aging (20-25℃): After crystal nuclei formation, continued low-temperature static aging prevents small particles from growing larger and coarser, maintaining a fine particle state. Only loose, soft agglomerates form between the particles, which can be easily dispersed later. This also allows the particles to form a porous structure, further increasing the specific surface area. S5. Surface modification: 3-aminopropyltriethoxysilane and polyethylene glycol 400 composite modifier were added to the silica suspension for modification, followed by pressure filtration, washing and drying to obtain silica.
[0007] Furthermore, to obtain a more stable effect, the silicon slag composition in step S1 is 65-75% SiO2, 8-12% F, 3-6% Al2O3, and 0.5-2.0% Fe2O3.
[0008] Furthermore, the activation conditions in step S1 are as follows: activation is performed in a planetary ball mill at a ball-to-material mass ratio of 5:1 to 8:1, a rotation speed of 300 to 500 rpm, and at a constant temperature for 1 to 3 hours; after activation, the silicon slag has a D50 ≤ 5 μm and a specific surface area ≥ 20 m². 2 / g.
[0009] Furthermore, in step S2, the composite alkaline solution contains 10-15% NaOH and 5-8% Na2CO3 by mass, and the liquid-solid ratio of activated silicon slag to alkaline solution is 4:1-6:1. The reaction conditions are 120-150℃, 0.2-0.4 MPa, and 200-300 rpm for 2-4 h.
[0010] Furthermore, the directional fluoride removal operation in step S3 is as follows: an AlCl3-CaCl2 composite defluorinating agent with a molar ratio of 1:2 to 1:3 is added to the sodium silicate filtrate, the amount of which is 1.1 to 1.3 times the molar fluoride content of the filtrate. The mixture is reacted at 40 to 60°C and 150 to 200 rpm for 30 to 60 minutes to generate a stable composite fluoride precipitate. The filtrate is then filtered to obtain a low-fluoride filtrate.
[0011] Furthermore, the chelation metal removal operation in step S3 is as follows: EDTA-2Na is added to the low-fluoride filtrate, the amount of which is 1.0 to 1.2 times the total molar content of aluminum and iron, the pH is adjusted to 8.5 to 9.0, and the reaction is carried out at a constant temperature of 50 to 70°C for 20 to 40 minutes. The metal ions form insoluble chelates, and the purified sodium silicate filtrate is obtained by filtration.
[0012] Furthermore, in step S4, the refined sodium silicate filtrate is diluted to a SiO2 mass concentration of 5-7% and a dilute sulfuric acid concentration of 15-20%. During nucleation, the mixture is stirred at a speed of 100-150 rpm for 30-40 min; and aged at 80-120 rpm for 60-90 min.
[0013] Furthermore, in step S5, the mass ratio of 3-aminopropyltriethoxysilane to polyethylene glycol 400 is 1:1 to 1:2, the amount of composite modifier added is 1.5 to 3.0% of the theoretical yield of silica, the modification is carried out at 40 to 50°C for 30 to 50 minutes, the filter residue after plate and frame filtration is washed by 6-stage countercurrent washing, and dried at 105 to 115°C for 4 to 6 hours to obtain the finished product.
[0014] Another object of the present invention is to provide a silica prepared by the above-described preparation method, wherein the silica product has a fluorine content as low as 27 ppm and a whiteness as high as 96.2%.
[0015] The chemical reaction processes involved in the preparation of this invention are as follows: The advantages of this invention are: 1. This invention abandons the traditional high-temperature calcination activation method and uses room-temperature mechanical activation to process raw materials, which generates no hydrogen fluoride gas and is clean, environmentally friendly and free of secondary pollution throughout the entire process; 2. This invention employs a NaOH-Na2CO3 composite buffer alkali system to achieve selective silicon dissolution. NaOH, as the main silicon dissolving agent, reacts with the silica in the silicon slag to generate soluble sodium silicate, thereby achieving efficient dissolution of the silicon component. Na2CO3 acts as a buffering agent, which can stabilize the alkalinity of the system, reduce corrosion of strong alkali equipment, and assist in improving the silica dissolution effect. It can also effectively inhibit the excessive dissolution of metals such as aluminum and iron, thus achieving selective silicon dissolution and synergistic control of impurities from the front end. 3. To address the problems of ion interference, severe co-precipitation, and insufficient impurity removal precision in traditional simultaneous defluorination and impurity removal processes, this invention adopts a staged impurity removal mode of first fixing fluoride and then chelating. An AlCl3-CaCl2 composite defluorinating agent is used to directionally capture and solidify fluoride ions in the feed solution, generating a structurally stable primary fluoride precipitate. Then, an EDTA-2Na chelating agent is used to precisely remove residual trace metal impurities from the liquid phase, avoiding the negative impact of co-precipitation. This achieves targeted impurity removal while stabilizing the fluoride precipitation system. In the finished product preparation stage, low-temperature nucleation coupled with low-temperature aging is used for synergistic molding: controllable nucleation is completed in the 30-40℃ range, with a slow reaction rate, generating a large number of fine silica nuclei, reducing particle surface activity, inhibiting hard agglomeration of grains, and reducing side reactions. Subsequent low-temperature aging at 20-25℃ effectively inhibits the coarsening and growth of fine grains, ensuring that the particles only form easily disintegrated, loose, soft agglomerates, and promoting the construction of a porous microstructure within the particles, thus improving the specific surface area and structural stability of the finished product. 4. To further improve the performance of the finished product, this invention adds a surface modification treatment for silica: a low-temperature in-situ modification of the suspension is performed using a compound modifier of KH-550 and PEG400. KH-550 can be grafted onto the surface of silica particles to eliminate hydrophilic groups, solving the problem of easy water absorption and agglomeration of the powder, while enhancing the compatibility of silica with organic substrates such as rubber and resin; PEG400 can uniformly coat the surface of the crystals, preventing particles from colliding and sticking together, and helping to improve the dispersion effect. Through the dual modification mechanism, the powder dispersibility and interfacial compatibility are improved simultaneously. After the modified material is filtered by plate and frame filter press, it is washed by six-stage countercurrent washing. The washing waste liquid can be recycled and reused to form a closed loop. Finally, it is dried at a constant temperature to obtain high-purity modified silica. 5. This process can achieve the harmless disposal of fluorine-containing silicon slag and the high-value recycling of fluorine and silicon resources, which has both good environmental value and economic benefits, and has broad prospects for industrial application. Detailed Implementation
[0016] The analysis and testing of raw material components and products involved in the embodiments of the present invention shall be carried out in accordance with the following requirements: Silica slag composition detection: Quantitative analysis was performed using X-ray fluorescence spectrometry (XRF). The mass fractions of SiO2, Fe2O3, and Al2O3 were directly given by the instrument's oxide quantitative results, and the F content was determined by the fluoride ion selective electrode method.
[0017] Calculation of silicon dissolution rate: X-ray fluorescence spectrometry was used to quantitatively analyze the silicon slag, and the total mass of silicon in the slag was calculated based on the feed amount. Ultraviolet spectrophotometry was used to analyze the sodium silicate filtrate collected after the composite alkali dissolution reaction to obtain the effective silicon mass dissolved in the liquid phase. The percentage of liquid-phase silicon mass to the total silicon mass of the silicon slag is the silicon dissolution rate, calculated using the formula: Dissolution rate = (Silicon content in filtrate / Total silicon content in silicon slag) × 100% Aluminum and iron removal rates were calculated as follows: The aluminum and iron content in the sodium silicate filtrate after composite alkali dissolution was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES). The Fe2O3 and Al2O3 contents in the silica slag were replaced with their corresponding aluminum and iron contents. The aluminum and iron removal rates were calculated as the percentage of the aluminum and iron content in the silica slag after subtracting the aluminum and iron content in the liquid phase from the aluminum and iron content in the silica slag. The formulas are: Aluminum removal rate = (Silica slag aluminum content - Silicate slag aluminum content) × 100% / Silicate slag aluminum content; Iron removal rate = (Silica slag iron content - Filtrate iron content) × 100% / Silicate slag iron content.
[0018] Silica purity, specific surface area, and whiteness testing: Silica purity was quantitatively analyzed using X-ray fluorescence spectrometry; the SiO2 mass percentage was used to determine the silica purity. Specific surface area was determined using a specific surface area analyzer according to GB / T 19587-2017 "Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method" via low-temperature nitrogen adsorption. Silica samples were tested using a whiteness meter; the blue light whiteness of the samples was determined according to GB / T 5950-2008 "Methods for Measuring Whiteness of Building Materials and Non-metallic Mineral Products," and the obtained value was the whiteness of the silica.
[0019] Example 1: A method for preparing high-purity low-fluorine silica, comprising the following steps: (1) Raw material pretreatment and mechanical activation: The mass composition of silicon slag is 70% SiO2, 10% F, 4.5% Al2O3 and 1.2% Fe2O3. Take 200g of silicon slag and place the silicon slag and zirconia grinding balls in a planetary ball mill for activation. The mass ratio of balls to silicon slag is 6:1. Activate at 400 rpm for 2 h. After activation, the silicon slag D50 is 4.15 μm and the specific surface area is 24.36 m² / g.
[0020] (2) Selective extraction of silicon components by composite alkali: Prepare a composite buffer alkali solution with a NaOH mass concentration of 12% and a Na2CO3 mass concentration of 6%. The liquid-solid ratio of activated silicon slag to alkali solution is 5:1. Place the solution in a closed high-pressure reactor and react for 3 h at 135 ℃, 0.3 MPa, and 250 rpm. Filter the solution under vacuum while hot to separate the iron and aluminum impurities from the filter residue. Collect the sodium silicate filtrate. The silicon dissolution rate is 92.37%, the residual silicon dioxide content in the filter residue is 3.15%, and the removal rates of iron and aluminum metal impurities are 94.12% and 93.58%, respectively, achieving efficient separation of silicon from iron and aluminum impurities.
[0021] (3) Graded and precise impurity removal treatment: ① Directional fluoride fixation: AlCl3-CaCl2 composite fluoride removal agent with a molar ratio of 1:1.25 was selected and added to sodium silicate filtrate at 1.2 times the total molar amount of fluoride in the filtrate. The reaction was carried out at 50 ℃ and 200 rpm for 45 min. After filtration, a low-fluoride filtrate was obtained with an F content of 41.25 mg / L and a fluoride removal rate of 99.61%. ② Chelation removal of metals: EDTA-2Na was added to the low-fluoride filtrate at an amount of 1.1 times the total molar amount of aluminum and iron. The pH was adjusted to 8.8 and the reaction was carried out at 60 ℃ for 30 min. After precision filtration, a refined sodium silicate filtrate was obtained with fluoride of 32.16 mg / L, aluminum of 1.84 mg / L, and iron of 0.27 mg / L.
[0022] (4) Low-temperature nucleation coupled with low-temperature aging: The refined sodium silicate filtrate was diluted to a SiO2 mass concentration of 6%, and 18% dilute sulfuric acid was slowly added dropwise at 35℃ to adjust the pH to 9.1. The mixture was stirred at 120 rpm for 30 min to generate uniform silica crystal nuclei. In the second stage, the temperature was lowered to 22℃, and the pH was further acidified to 6.8. The mixture was then aged at a low speed of 120 rpm for 60 min to obtain a silica suspension. The main components of this silica suspension were solid-phase hydrated silica and liquid-phase sodium sulfate aqueous solution. The effective solid content of solid silica in the suspension was 6.00%, and the liquid phase contained trace impurity ions (F... - 18.72 mg / L, Al 3+ 0.95 mg / L, Fe 3+ (0.14 mg / L).
[0023] (5) Surface modification treatment: KH-550 and polyethylene glycol 400 composite modifier with a mass ratio of 1:1.15 were added to the suspension. The amount added was 2.20% of the theoretical yield of silica. The modification was carried out at 40 ℃ for 30 min. After plate and frame filtration, the filter residue was washed by 6 stages of countercurrent washing and dried at 110 ℃ for 4 h to obtain SiO2 99.5%, fluorine 28 ppm, and specific surface area of 415 m². 2 Finished silica product with a whiteness of 96.2% and a weight of 0.5g.
[0024] Example 2: A method for preparing high-purity low-fluorine silica, comprising the following steps: (1) Raw material pretreatment and mechanical activation: The mass composition of silicon slag is 68% SiO2, 9.5% F, 4.2% Al2O3, and 1.4% Fe2O3. Take 200 g of silicon slag and place the silicon slag and zirconia grinding balls in a planetary ball mill for activation. The mass ratio of balls to silicon slag is 7:1. Activate at 420 rpm for 2 h. After activation, the silicon slag D50 is 3.5 μm and the specific surface area is 22.18 m² / g.
[0025] (2) Selective extraction of silicon components by composite alkali: Prepare a composite buffer alkali solution with a NaOH mass concentration of 13% and a Na2CO3 mass concentration of 6.5%; the liquid-solid ratio of activated silicon slag to alkali solution is 4.5:1, and place it in a closed high-pressure reactor and react at 130 ℃, 0.28 MPa, and 220 rpm for 2.5 h; filter while hot under vacuum to separate the filter residue containing iron and aluminum impurities, collect the sodium silicate filtrate, the silicon dissolution rate is 93.68%, the residual silicon dioxide content in the filter residue is 3.20%, and the removal rates of iron and aluminum metal impurities are 94.25% and 93.80%, respectively, achieving efficient separation of silicon from iron and aluminum impurities.
[0026] (3) Graded and precise impurity removal treatment: ① Directional fluoride fixation: AlCl3-CaCl2 composite fluoride remover with a molar ratio of 1:1.22 was selected and added to sodium silicate filtrate at 1.2 times the total molar amount of fluoride in the filtrate. The reaction was carried out at 55 ℃ and 180 rpm for 50 min. After filtration, a low-fluoride filtrate was obtained with an F content of 40.82 mg / L and a fluoride removal rate of 99.59%. ② Chelation removal of metals: EDTA-2Na was added to the low-fluoride filtrate at an amount of 1.1 times the total molar amount of aluminum and iron. The pH was adjusted to 8.7 and the reaction was carried out at 62 ℃ for 35 min. After precision filtration, a refined sodium silicate filtrate was obtained with fluoride of 31.56 mg / L, aluminum of 2.01 mg / L, and iron of 0.31 mg / L.
[0027] (4) Low-temperature nucleation coupled with low-temperature aging: The refined sodium silicate filtrate was diluted to a SiO2 mass concentration of 6%; 16% dilute sulfuric acid was slowly added dropwise at 35 ℃ to adjust the pH to 9.3, and stirred at 100 rpm for 40 min to generate uniform silica crystal nuclei. In the second stage, the temperature was lowered to 22 ℃, and the pH was further acidified to 6.6. The suspension was aged at 100 rpm for 70 min to obtain a silica suspension. The main components of the silica suspension were solid-phase hydrated silica and liquid-phase sodium sulfate aqueous solution. The effective solid content of solid silica in the suspension was 6.00%, and the liquid phase contained trace impurity ions (F). - 29.45 mg / L, Al 3+ 1.52 mg / L, Fe 3+ (0.22 mg / L).
[0028] (5) Surface modification treatment: A composite modifier of KH-550 and polyethylene glycol 400 with a mass ratio of 1:1.16 was added to the suspension. The amount added was 2.1% of the theoretical yield of silica. The modification was carried out at 44 ℃ for 38 min. After plate and frame filtration, the filter residue was washed with countercurrent for 6 stages until the conductivity of the filtrate was 36.42 μS / cm. The residue was dried at 110 ℃ for 5 h to obtain 99.5% SiO2, 27 ppm fluorine, and a specific surface area of 413 m². 2 Finished silica product with a whiteness of 96.1% and a weight of 0.5g.
[0029] Comparative Example 1 (1) Raw material pretreatment and mechanical activation: The mass composition of silicon slag is 70% SiO2, 10% F, 4.5% Al2O3 and 1.2% Fe2O3. Take 200 g of silicon slag and place the silicon slag and zirconia grinding balls in a planetary ball mill for activation. The mass ratio of balls to silicon slag is 6:1. Activate at 400 rpm for 2 h. After activation, the D50 of silicon slag is 4.15 μm and the specific surface area is 24.36 m² / g.
[0030] (2) Selective extraction of silicon components by single alkali solution: Prepare a single alkali solution with a mass concentration of 12% sodium hydroxide without adding sodium carbonate; the liquid-solid ratio of activated silicon slag to alkali solution is 5:1, and it is placed in a closed high-pressure reactor and reacted at 135℃, 0.3 MPa and 250 rpm for 3 h; filter while hot under vacuum to separate the filter residue containing iron and aluminum impurities, collect the sodium silicate filtrate, the silicon dissolution rate is 81%, and the removal rates of iron and aluminum metal impurities are 46.2% and 41.5% respectively.
[0031] (3) Graded and precise impurity removal treatment: ① Directional fluoride fixation: AlCl3-CaCl2 composite fluoride removal agent with a molar ratio of 1:1.25 was selected and added to sodium silicate filtrate at 1.2 times the total molar amount of fluoride in the filtrate. The reaction was carried out at 50 ℃ and 200 rpm for 45 min. After filtration, a low-fluoride filtrate was obtained with an F content of 186.32 mg / L and a fluoride removal rate of 97.24%. ② Chelation removal of metals: EDTA-2Na was added to the low-fluoride filtrate at an amount of 1.1 times the total molar amount of aluminum and iron. The pH was adjusted to 8.8 and the reaction was carried out at 60 ℃ for 30 min. After precision filtration, a refined sodium silicate filtrate was obtained with 184.72 mg / L of fluoride, 6.32 mg / L of aluminum, and 1.15 mg / L of iron.
[0032] (4) Low-temperature nucleation coupled with low-temperature aging: The refined sodium silicate filtrate was diluted to a SiO2 mass concentration of 6%, and 18% dilute sulfuric acid was slowly added dropwise at 35°C to adjust the pH to 9.1. The mixture was stirred at 120 rpm for 30 min to generate uniform silica crystal nuclei. In the second stage, the temperature was lowered to 22°C, and the pH was further acidified to 6.8. The mixture was then aged at a low speed of 120 rpm for 60 min to obtain a silica suspension. The main components of this silica suspension were solid-phase hydrated silica and liquid-phase sodium sulfate aqueous solution. The effective solid content of solid silica in the suspension was 5.35%, and the liquid phase contained trace impurity ions (F... - 181.26 mg / L, Al 3+ 6.11 mg / L, Fe 3+ (1.11 mg / L).
[0033] (5) Surface modification treatment: KH-550 and polyethylene glycol 400 composite modifier with a mass ratio of 1:1.15 were added to the suspension. The amount added was 2.20% of the theoretical yield of silica. The modification was carried out at 40℃ for 30 min. After plate and frame filtration, the filter residue was washed by countercurrent for 6 stages until the conductivity of the filtrate was ≤68.2 μS / cm. The residue was dried at 110℃ for 4 h to obtain silica product with SiO2 96.5%, fluorine 365 ppm, specific surface area 268 m² / g, and whiteness 90.6%.
[0034] Compared to Example 1, Comparative Example 1 used only a 12% sodium hydroxide solution in the alkali dissolution stage, without adding sodium carbonate buffer, while the remaining process steps and parameters were completely identical. The results showed that the alkali dissolution system lacking sodium carbonate buffer significantly reduced both process efficiency and product quality. Due to the lack of alkalinity buffering capacity in the single sodium hydroxide alkali system, the OH⁻ concentration fluctuated greatly during the reaction, failing to provide a stable reaction environment for silica leaching. The final silica leaching rate was only 81%, significantly lower than the composite alkali system in Example 1. Simultaneously, under strong alkali conditions, iron and aluminum impurities in the silica slag were more easily dissolved into the liquid phase. After alkali dissolution filtration, the removal rates of iron and aluminum impurities were only 46.2% and 41.5%, respectively. A large amount of impurities entered subsequent processes with the sodium silicate filtrate. Even with the same directional fluorine fixation, chelation impurity removal, nucleation aging, and modified washing processes, the final precipitated silica product still had a fluorine residue as high as 365 ppm, and the silica purity was only 96.5%, failing to meet the requirements for high-grade products. This indicates that sodium carbonate and sodium hydroxide have a clear synergistic effect. Sodium carbonate can stabilize the alkalinity of the system and improve the silicon dissolution efficiency through the buffering effect. It can also help to form insoluble carbonates with metal impurities by using carbonate ions, thereby simultaneously retaining impurities during the alkaline dissolution stage. This reduces the impurity removal load at the source and is a key additive to ensure product purity and quality.
Claims
1. A method for preparing high-purity, low-fluorine silica, characterized in that, Includes the following steps: S1. Raw material pretreatment and activation: Place the silicon slag in a ball mill for ball milling and activation; S2. Selective extraction of silicon components by composite alkali: NaOH and Na2CO3 are prepared into a composite alkali solution. The activated silicon slag is mixed with the composite alkali solution and reacted under closed conditions. The reaction solution is then filtered and the sodium silicate filtrate is collected. S3. Filtrate fractionation and impurity removal: This includes two-stage impurity removal, namely directional fluoride fixation and chelation metal removal, to obtain refined sodium silicate filtrate; S4. Nucleation and aging: After diluting the refined sodium silicate filtrate, dilute sulfuric acid is added dropwise at 30~40℃ to acidify it, and the pH is adjusted to 9.0~9.
5. Stirring is carried out to generate silicate crystal nuclei; then the temperature is lowered to 20~25℃, and acidification is continued to adjust the pH to 6.5~7.
0. Aging is carried out to obtain a silicate suspension. S5. Surface modification: 3-aminopropyltriethoxysilane and polyethylene glycol 400 composite modifier were added to the silica suspension for modification, followed by pressure filtration, washing and drying to obtain silica.
2. The preparation method according to claim 1, characterized in that: The silicon slag in step S1 is composed of 65-75% SiO2, 8-12% F, 3-6% Al2O3, and 0.5-2.0% Fe2O3.
3. The preparation method according to claim 1, characterized in that: The activation condition in step S1 is: in a planetary ball mill, the mass ratio of ball to material is 5:1-8:1, the rotation speed is 300-500 rpm, and the constant temperature activation time is 1-3 h; after activation, the D50 of the silicon slag is ≤5 μm, and the specific surface area is ≥20 m 2 / g.
4. The preparation method according to claim 1, characterized in that: In step S2, the composite alkaline solution contains 10-15% NaOH and 5-8% Na2CO3 by mass, and the liquid-solid ratio of activated silicon slag to alkaline solution is 4:1-6:
1. The reaction conditions are 120-150℃, 0.2-0.4 MPa, and 200-300 rpm for 2-4 h.
5. The preparation method according to claim 1, characterized in that: The directional fluoride removal operation in step S3 is as follows: an AlCl3-CaCl2 composite fluoride removal agent with a molar ratio of 1:2 to 1:3 is added to the sodium silicate filtrate, the amount of which is 1.1 to 1.3 times the molar fluoride content of the filtrate. The mixture is reacted at 40 to 60°C and 150 to 200 rpm for 30 to 60 minutes, and then filtered to obtain a low-fluoride filtrate.
6. The preparation method according to claim 1, characterized in that: The chelation metal removal operation in step S3 is as follows: EDTA-2Na is added to the low-fluoride filtrate, the amount of which is 1.0 to 1.2 times the total molar content of aluminum and iron, the pH is adjusted to 8.5 to 9.0, the reaction is carried out at a constant temperature of 50 to 70°C for 20 to 40 minutes, and then filtered to obtain refined sodium silicate filtrate.
7. The preparation method according to claim 1, characterized in that: In step S4, the refined sodium silicate filtrate is diluted to a SiO2 mass concentration of 5-7% and a dilute sulfuric acid concentration of 15-20%. During nucleation, the mixture is stirred at 100-150 rpm for 30-40 min; and aged at 80-120 rpm for 60-90 min.
8. The preparation method according to claim 1, characterized in that: In step S5, the mass ratio of 3-aminopropyltriethoxysilane to polyethylene glycol 400 is 1:1 to 1:2, the amount of composite modifier added is 1.5 to 3.0% of the theoretical yield of silica, the modification is carried out at 40 to 50°C for 30 to 50 minutes, the filter residue after plate and frame filtration is washed by 6-stage countercurrent washing, and dried at 105 to 115°C for 4 to 6 hours to obtain the finished product.
9. The silica prepared by the method according to any one of claims 1-8, characterized in that: The fluorine content in the silica product is as low as 27 ppm, and the whiteness is as high as 96.2%.
